2014
DOI: 10.1186/1475-2875-13-353
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide-treated nets ownership and utilization among under-five children following the 2010 mass distribution in Burkina Faso

Abstract: BackgroundPeriodic mass distributions contribute significantly to universal access to insecticide-treated nets (ITNs). However, due to the limited number of nets distributed, needs remain unsatisfied, particularly in large households.MethodsThis study was conducted in Kaya health district following the 2010 mass distribution of ITNs in Burkina Faso. Data were collected on the socio-economic and geo-spatial characteristics and ITN possession and utilization levels of 2,004 households. The study explored: 1) ITN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…The finding was in line with slight difference with the study from Southern Ethiopia, which was 27.2% (15). However, it was boldly lower than a study conducted in malaria endemic areas of Raya Alamata District, Ethiopia 71% and in Burkina Faso, 70% (13, 22). The possible explanation for such discrepancies could be geographical variations, the time gap between distributions of ITNs, and survey period and also other age groups might be utilized as evidenced in these studies (6).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The finding was in line with slight difference with the study from Southern Ethiopia, which was 27.2% (15). However, it was boldly lower than a study conducted in malaria endemic areas of Raya Alamata District, Ethiopia 71% and in Burkina Faso, 70% (13, 22). The possible explanation for such discrepancies could be geographical variations, the time gap between distributions of ITNs, and survey period and also other age groups might be utilized as evidenced in these studies (6).…”
Section: Discussionmentioning
confidence: 57%
“…This is consistent with findings from Ethiopia and Kenya (10, 17). In contrary from Ethiopian and Kenyan study evidences, a study conducted at Burkina Faso showed that family size showed no significant difference in under five ITNs utilization (22). The possible explanations for this might be in proportionate family size with the number of bed rooms or separate sleeping space.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[3] Mi ssing for one mosquito i n the PPF-LLIN arm. [4] See methods for es timation details. Grey horizontal bands indicate the four surveys that were conducted during the trial (see Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is also one of the few countries with no significant association between LLIN ownership and reduction in child mortality . 3 Even though approximately 90% of households in 2013 owned at least one LLIN, 4,5 national surveys show little impact on Plasmodium falciparum prevalence, with 61% of children aged six months to five years infected in 2014. 5 One possible reason for the lack of impact in the past and the rising number of cases in recent years is the increasing insecticide resistance in vectors seen in Burkina Faso 6 and across most of sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%